1988
DOI: 10.1111/j.1365-2621.1988.tb00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Guava puree with reduced stone cell content: preparation and characteristics of concentrates and nectars

Abstract: A decanter centrifuge was used to decrease the content of stone cells in guava puree before evaporation. Concentration factors between 3.3-and 4.3-fold were achieved. Thirty-seven per cent of the stone cells could be removed in a small decanter, whereas virtually all sclereids are removed on an industrial scale. Small significant increases in moisture contents, total soluble solids and titratable acidity and decreases in pectin fractions and ascorbic acid contents (average 38%) occurred during processing; guav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…After textural measurements, guavas were hand‐peeled and cut in small pieces then introduced into a fruit pulper with a 0.85‐mm mesh. Seeds were removed to avoid interferences on the rheological measurements (Weinert and Vanwyk 1988).…”
Section: Methodsmentioning
confidence: 99%
“…After textural measurements, guavas were hand‐peeled and cut in small pieces then introduced into a fruit pulper with a 0.85‐mm mesh. Seeds were removed to avoid interferences on the rheological measurements (Weinert and Vanwyk 1988).…”
Section: Methodsmentioning
confidence: 99%
“…Work previously carried out by our team has shown that guava pericarp contains heterogeneous tissues consisting of two main cell types: parenchyma cells and stone cells [5]. Stone cells are surrounded by very thick secondary walls and they are responsible for the grainy mouthfeel when the fresh fruit or products derived from them are consumed [4]. The predominant structural cell wall compounds in stone cells are mainly cellulose, acetylated xylans and lignin [5].…”
Section: Introductionmentioning
confidence: 99%
“…Up until now, enzyme treatments of guava puree were performed rather empirically and their effects on the cell walls and the polysaccharides present in the soluble fraction have not been elucidated [3]. [4] showed a high decrease in water-soluble, oxalate-soluble and alkali-soluble pectic fractions when the fruit was subjected to pectinolytic treatment.…”
Section: Introductionmentioning
confidence: 99%